NGHIÊN CỨU ẢNH HƯỞNG CỦA BỘT NHÔM ĐẾN MỘT SỐ TÍNH CHẤT CỦA THUỐC NỔ NHŨ TƯƠNG - Nguyễn, Văn Tính; Đàm, Quang Sáng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EFFECT OF ALUMINUM POWDER ON SOME PROPERTIES OF EMULSION EXPLOSIVE The article studies the effect of aluminum powder (with different content and particle size) on some significant properties of emulsion explosive such as density, water resistance, detonation velocity and heat of explosion. The calculated data and experimental results show that the density, heat of explosion and detonation velocity of the emulsion explosive with aluminum powder as an energy additive which is less than 10% of the content are higher than those without aluminum powder, while its water resistance decreases. It is proved that aluminum powder can be completely used to impove the detonation energy of emulsion explosive with paying attention to its low water resistance when conduct underwater blasting.